Dye and its Removal from aqueous solution by Adsorption: A review (International Journal of Food and Nutritional Sciences, 2022)
The removal of dyes from waste water is a matter of great interest in the field of waste water treatment. The effluents from many industries often contain one or more toxic dyes. Therefore, an increased interest has been focused on removing such dyes from wastewaters. In general, several methods are used for the removal of dyes from waste water. Different techniques including chemical oxidation, precipitation, membrane filtration, ion exchange, biosorption and adsorption are adopted to remove dyes from aqueous solution. Adsorption has gained attraction in the treatment of dyes from coloured wastewater compared to other techniques due to the bulk availability of adsorbents, higher dye uptake capabilities, robustness and economical desorption cycles and excellent resistance towards degenerative action of a target contaminant (Gupta et al., 2013). Also, adsorption using bio-derived, renewable sorbent materials can be seen as environmental friendly and can provide us with a trouble –free, commercially cheap operation. This chapter describes the comparative dye adsorption potential of various waste biomass adsorbents reported in the literature for treatment of basic (cationic), acidic, direct and reactive dyes.